2018
DOI: 10.1016/j.jveb.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward nonhuman animals and their welfare: Do behaviorists differ from other veterinarians?

Abstract: Veterinarians are an important source of information about animal care for owners. They provide general advice about topics important to an animal's well-being, such as appropriate training, exercise and nutrition. Veterinary behaviorists, when dealing with undesired or abnormal behaviors, also perform an assessment of pet welfare and an evaluation of owners' behavior and attitudes. It is likely that these assessments are affected by the attitude toward animals and toward animal welfare of the behaviorists. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The utility that certain animals have for man does not seem to evoke this kind of response—lab mice and rats, despite their utility and relative closeness, do not evoke affection or concern for their condition [ 39 ]. It is remarkable that in the current study, a different attitude towards livestock versus pet welfare was found for the Brambell Report’s Five Freedoms with regard to those freedoms that involve the psychological aspects of welfare [ 9 ]. As for other categories of people, even veterinary students seem to distinguish between “animals good to think with” and “animals good to eat” [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The utility that certain animals have for man does not seem to evoke this kind of response—lab mice and rats, despite their utility and relative closeness, do not evoke affection or concern for their condition [ 39 ]. It is remarkable that in the current study, a different attitude towards livestock versus pet welfare was found for the Brambell Report’s Five Freedoms with regard to those freedoms that involve the psychological aspects of welfare [ 9 ]. As for other categories of people, even veterinary students seem to distinguish between “animals good to think with” and “animals good to eat” [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This will indirectly increase farm animals’ welfare, preventing animal health-related threats and minimizing environmental impacts, in support of the EU Sustainable Development Strategy [ 49 ]. A more structured teaching animal welfare in veterinary curricula is also required for those students who will deal with small animals in the future [ 50 ], especially if their specialization does not include behaviour [ 9 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal Attitude Scale (AAS), developed by Herzog, Betchart, and Pittman' [25], contained 20 items measured by 5-point-Likert scale. The AAS has been used to study adult's attitudes toward animals [26,27]. Knight, Vrij, Cherryman, and Nunkoosing [28] measured students' attitudes through 4 aspects including their attitude toward using animals for experimentation, using animals in the classroom, using animals for personal decoration, and using animals for entertainment.…”
Section: Attitudes Toward Animals: From Nonhuman To Humanmentioning
confidence: 99%